1999
DOI: 10.1128/mcb.19.4.2803
|View full text |Cite
|
Sign up to set email alerts
|

Specific Binding of High-Mobility-Group I (HMGI) Protein and Histone H1 to the Upstream AT-Rich Region of the Murine Beta Interferon Promoter: HMGI Protein Acts as a Potential Antirepressor of the Promoter

Abstract: The high-mobility-group I (HMGI) protein is a nonhistone component of active chromatin. In this work, we demonstrate that HMGI protein specifically binds to the AT-rich region of the murine beta interferon (IFN-␤) promoter localized upstream of the murine virus-responsive element (VRE). Contrary to what has been described for the human promoter, HMGI protein did not specifically bind to the VRE of the murine IFN-␤ promoter. Stably transfected promoters carrying mutations on this HMGI binding site displayed del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 52 publications
3
48
0
Order By: Relevance
“…For example, treatment with this drug has resulted in the repression of the mouse mammary tumor virus (MMTV) and ␤-interferon (IFN-␤) gene promoters (50,69). However, at 75 g/ml DST, we have detected no significant alteration to the expression activities of any of the genes residing at the 10q25 neocentromere.…”
Section: Discussionmentioning
confidence: 57%
“…For example, treatment with this drug has resulted in the repression of the mouse mammary tumor virus (MMTV) and ␤-interferon (IFN-␤) gene promoters (50,69). However, at 75 g/ml DST, we have detected no significant alteration to the expression activities of any of the genes residing at the 10q25 neocentromere.…”
Section: Discussionmentioning
confidence: 57%
“…Distinct mechanisms for how the antirepressor antagonizes repressor activity include the following: (a) direct protein-protein association without any DNA binding by the antirepressor (42)(43)(44)(45); (b) exclusion of the repressor by DNA binding of the antirepressor (46); and (c) proteolysis of the repressor promoted by the antirepressor (47). Our data have revealed that the monomeric CarS, which does not itself bind DNA, physically interacts with CarA.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid constructions were carried out by double PCR as previously described (3) by using plasmid pBLCAT3-muIFN-␤ wt330 as a template. This plasmid carries the wild-type murine IFN-␤ (muIFN-␤) promoter fragment from Ϫ330 to ϩ20 cloned in front of the CAT reporter gene of plasmid pBLCAT3 (3). For primers, we used the corresponding mutated oligonucleotides described in Table 1 as well as primer Ϫ40 (5Ј-GTTTTCCCAGTCACGAC-3Ј) and primer CAT (5Ј-CCATTTTAGCTTCCTTAG-3Ј).…”
Section: Methodsmentioning
confidence: 99%
“…A strong HMGI binding site is present in the muIFN-␤ promoter next to the YY1-binding site present at position Ϫ122, and disruption of this site has been determined to lead to a reduced promoter activity (3). In order to test the eventual effect of the mutation in strain mut122 on the DNA-binding capacity of protein HMGI to the IFN-␤ promoter, gel retardation experiments were carried out with wt330, mut90, and mut122 promoters (from position Ϫ330 to ϩ20) and recombinant HMGI protein.…”
Section: Yy1 Binds To the Muifn-␤ Promotermentioning
confidence: 99%